TROCAS GASOSAS DE PLANTAS JOVENS DE TAXI-BRANCO SUBMETIDAS À VARIAÇÃO DE TEMPERATURA FOLIAR E SUSPENSÃO DA IRRIGAÇÃO - Ronaldo Ribeiro de Morais; Luiz Marcelo Brum Rossi; Rosana Clara Victoria Higa (Ciência Florestal, 2017)
The study aimed to investigate the influence of leaf temperature variation associated with irrigation suspension on gas exchange of seedlings of Sclerolobium paniculatum Vogel. The study was carried out in a greenhouse at experimental area of Embrapa, Amazônia Ocidental. Plants were grown in a greenhouse and, after four months were subjected to three treatments (irrigated maintained until the field capacity, irrigation suspended for eight and 14 days). We evaluated the physiological parameters of gas exchange, net assimilation rate of CO2 (A), leaf transpiration (E), stomatal conductance (gs) and water use efficiency (WUE) which were obtained through a photosynthesis portable meter (CI-340, CID, Inc). The results showed reduction of net assimilation rate of CO2 depending on the elevation of the leaf temperature and without irrigation. After eight days without irrigation, decreased rates of photosynthetic assimilation of CO2 in 62, 65, 75, 58, 50 and 64%, and after 14 days the reduction was 80, 85, 85, 84, 86 and 93% compared to plants irrigated maintained at temperatures of 25, 30, 35, 40, 45 and 50 °C, respectively. The leaf transpiration was inversely proportional to rates of net photosynthetic assimilation of CO2, which has increased with an increased leaf temperature. The physiological behavior of gas exchange of Sclerolobium paniculatum showed variations both as regards to the effect of leaf temperature as the suspension of irrigation.